PENGARUH MODEL PEMBELAJARAN REALISTIC MATHEMATIC EDUCATION (RME) TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS V SDN 005 LANGGINI - Aini Fadila, Nurul; Amir Luthfi; Muhammad Syahrul Rizal; Afriza Rahma Rani; Mufarizuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research shows that the problem-solving ability of fifth-grade students is still low; students have difficulty in understanding problems, planning, implementing the solution, and drawing conclusions on mathematical word problems. The objective of this study is to determine the extent of the influence of the Realistic Mathematic Education (RME) learning model on the mathematical problem-solving ability of fifth-grade students at SDN 005 Langgini compared to the Problem Based Learning (PBL) model. The method used in this research is a quasi-experiment with a Pretest-Posttest Control Group Design. The research population was all fifth-grade students at SDN 005 Langgini, with Class 5B designated as the experimental group applying the RME model, and Class 5A as the control group using the PBL model. The data collection techniques used were observation and tests (pretest and posttest). Data analysis was performed using the normality test, homogeneity test, and hypothesis testing (t-test). The results of the t-test on the posttest data show a significance value (Sig. 2-tailed) of 0.026. Since the significance value of 0.026 is smaller than 0.05, it can be concluded that there is a statistically significant difference between the average problem-solving abilities of the experimental group and the control group. This indicates that the Realistic Mathematic Education (RME) Learning Model has a significant influence on the improvement of the problem-solving ability of fifth-grade students at SDN 005 Langgini.